2016
DOI: 10.3390/rs8010072
|View full text |Cite
|
Sign up to set email alerts
|

Inter-Comparison of S-NPP VIIRS and Aqua MODIS Thermal Emissive Bands Using Hyperspectral Infrared Sounder Measurements as a Transfer Reference

Abstract: This paper compares the calibration consistency of the spectrally-matched thermal emissive bands (TEB) between the Suomi National Polar-orbiting Partnership (S-NPP) Visible Infrared Imaging Radiometer Suite (VIIRS) and the Aqua Moderate Resolution Imaging Spectroradiometer (MODIS), using observations from their simultaneous nadir overpasses (SNO). Nearly-simultaneous hyperspectral measurements from the Aqua Atmospheric Infrared Sounder(AIRS) and the S-NPP Cross-track Infrared Sounder (CrIS) are used to account… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 20 publications
2
11
0
Order By: Relevance
“…Specifically, only the channels with a quality assurance value less than 3 were used. Similar approaches have been used for various other studies and therefore been confirmed as an efficient and reliable method suitable for the MODIS‐AIRS intercalibration study here (Efremova et al, ; Li et al, ; Li et al, ; A. Wu et al, ). The Simultaneous Nadir Overpass (SNO) data sets of IASI and MODIS are collected from two pairs of IASI footprints from each side of nadir and MODIS pixels in a range of ±10° near the nadir frame.…”
Section: Application On Real Airs/modis Datasupporting
confidence: 57%
See 1 more Smart Citation
“…Specifically, only the channels with a quality assurance value less than 3 were used. Similar approaches have been used for various other studies and therefore been confirmed as an efficient and reliable method suitable for the MODIS‐AIRS intercalibration study here (Efremova et al, ; Li et al, ; Li et al, ; A. Wu et al, ). The Simultaneous Nadir Overpass (SNO) data sets of IASI and MODIS are collected from two pairs of IASI footprints from each side of nadir and MODIS pixels in a range of ±10° near the nadir frame.…”
Section: Application On Real Airs/modis Datasupporting
confidence: 57%
“…Specifically, only the channels with a quality assurance value less than 3 were used. Similar approaches have been used for various other studies and therefore been confirmed as an efficient and reliable method suitable for the MODIS-AIRS intercalibration study here (Efremova et al, 2014;Li et al, 2013;Li et al, 2016;A. Wu et al, 2012).…”
Section: 1029/2018jd028585mentioning
confidence: 59%
“…The RSR correction factor is derived as a radiance ratio between S-VIIRS and A-MODIS theoretical values, derived from RSR integration using AIRS hyper-spectral data. Results from the work reported in [23] indicate that the RSR correction reduces the differences by approximately 0.10 K and 0.29 K for M15/B31 and M16/B32 respectively. For M14/B29, since there is not enough spectral coverage for both A-AIRS and S-Cross track Infrared Sounder (CrIS), there is no RSR factor derived for this band.…”
Section: Calibration Consistencymentioning
confidence: 90%
“…The remaining bias does point to the inadequacy of the calibration model of S-VIIRS. The impacts of spectral correction for the RSR differences using measured simultaneous hyper-spectral data from A-Atmospheric Infrared Sounder (AIRS) for M15/B31 and M16 B32 are described in [23]. The RSR correction factor is derived as a radiance ratio between S-VIIRS and A-MODIS theoretical values, derived from RSR integration using AIRS hyper-spectral data.…”
Section: Calibration Consistencymentioning
confidence: 99%
“…The Visible Infrared Imaging Radiometer Suite (VIIRS) onboard the same platform is a filter radiometer with 17 visible/near‐infrared and 5 infrared (IR) spectral bands between 0.412 and 12.01 μm, collecting imagery and radiometric data of the Earth and its atmosphere (Cao et al, ; De Luccia et al, ; Hillger et al, ). With its high radiometric accuracy and spatial resolution (750 m for moderate‐resolution bands [M bands] and 375 m for imaging resolution bands [I bands] at nadir), VIIRS continues the heritage measurements from the Advanced Very High Resolution Radiometer (AVHRR) on Polar Operational Environmental Satellites (POES), the Operational Linescan System (OLS) on Defense Meteorological Satellite Program (DMSP; Elvidge et al, ), and the Moderate Resolution Imaging Spectroradiometer (MODIS) on the Terra and Aqua satellites (Cao et al, ; Li et al, ; Liang & Ignatov, ; Madhavan et al, ). More than 20 Environmental Data Records (EDR), such as sea surface temperature (SST), cloud properties, and fires, are produced from the calibrated VIIRS SDR (Cao et al, ; Liu et al, ; Xiong et al, ).…”
Section: Introductionmentioning
confidence: 99%